A inclusão digital como direito fundamental passível de viabilizar a participação cidadã - Flain, Valdirene Silveira (2017)
The development of Information and Communication Technologies (ICT) has transformed the way of life and the way people relate, impacting human life in every way. So everyone needs to be connected. ICT has become an important tool because of the infinite benefits to human development. Thus, digital inclusion has become a necessity, a new right in contemporary society. However, it is known that not all citizens have access to these benefits. A large portion of the Brazilian population, economically disadvantaged, is excluded and unable, even, to exercise full citizenship. This is due to the historical indices of inequality in Brazil, the inefficiency of the State in the realization of fundamental rights, and the ineffective and disarticulated public policies of digital inclusion. It is understood that public policies that only give access to the equipment are not the best solution to the problem. The process of digital inclusion must be more complex, in addition to access to equipment, must take into account the education, appropriation and adaptation of these technologies to human needs, serving as a condition and means for the realization of other fundamental rights. In this perspective, considering that fundamental rights are gradual achievements, stemming from historical struggles for equality as a function of social development, the present research aims to answer the following question: should digital inclusion be expressly recognized by the Federal Constitution as a right Fundamental, linked to human dignity, in Brazil? In addition, the research intends to verify the possibility of digital inclusion being recognized as a fundamental right linked to the dignity of the human person, becoming a viable means of citizen participation. To address the issue, this research was divided into two parts. The first deals with the foundations that make digital inclusion a fundamental right, linked to the dignity of the human person, which will allow us to understand, from the recognition of all the benefits of these technologies for human development and the exercise of citizenship, the need To recognize, expressly, as a new fundamental right. In this part, the method of inductive approach will be used, which is more adequate to identify and present the concepts, meanings, benefits and potential of digital inclusion. In addition to analyzing the possibilities of recognition of digital inclusion as a fundamental right linked to the dignity of the human person, from the perspective of the foundations of the current Democratic State of Law, presents an overview of the actions of digital inclusion in Brazil. In the second part, digital inclusion is approached as a fundamental right capable of enabling citizen participation in contemporary society. In this part, the dialectical method will be used, which will allow visualizing the development of ICT and digital inclusion in a set of processes, uninterrupted changes, mutual influence and progressive development. Because it will provide an understanding of the influence of digital inclusion in the implementation of other fundamental rights and citizen participation, in addition to enabling a more active and vigilant citizenship, becoming a tool of resistance, relevant in facing all types of exclusion .